The influence of microgravity on Euglena gracilis as studied on Shenzhou 8. (8th August 2013) - Nasir, A.; Strauch, S. M.; Becker, I.; Sperling, A.; Schuster, M.; Richter, P. R.; Weißkopf, M.; Ntefidou, M.; Daiker, V.; An, Y. A.; Li, X. Y.; Liu, Y. D.; et al.
Abstract: The German Aerospace Center (DLR) enabled German participation in the joint space campaign on the unmanned Shenzhou 8 spacecraft in November 2011. In this report, the effect of microgravity on Euglena gracilis cells is described. Custom‐made dual compartment cell fixation units (containing cells in one chamber and fixative – RNA lysis buffer – in another one) were enclosed in a small container and placed in the Simbox incubator, which is an experiment support system. Cells were fixed by injecting them with fixative at different time intervals. In addition to stationary experiment slots, Simbox provides a 1 g reference centrifuge. Cell fixation units were mounted in microgravity and 1 g reference positions of Simbox. Two Simbox incubators were used, one for space flight and the other as ground reference. Cells were fixed soon after launch and shortly before return of the spaceship. Due to technical problems, only early in‐flight samples (about 40 min after launch microgravity and corresponding 1 g reference) were fully mixed with fixative, therefore only data from those samples are presented. Transcription of several genes involved in signal transduction, oxidative stress defence, cell cycle regulation and heat shock responses was investigated with quantitative PCR. The data indicate that Euglena cells suffer stress upon short‐term exposure to microgravity; various stress‐induced genes were up‐regulated. Of 32 tested genes, 18 were up‐regulated, one down‐regulated and the rest remained unaltered. These findings are in a good agreement with results from other research groups using other organisms.